Pemberdayaan Keluarga dan Masyarakat dalam Pencegahan dan Aplikasi Akupunktur pada Nyeri Muskuloskeletal di Bibis Luhur Nusukan Banjarsari Surakarta - Purwanto; Eka Deviany Widyawaty; Rifki Ahmad (Rena Cipta Mandiri, 2024)
MSDs (Musculoskeletal Diseases) are disorders of the musculoskeletal system, including joints, nerves, muscles, and the spine, often caused by unnatural work activities. These pains can be managed through various methods such as medication, relaxation therapy, physical therapy, and acupuncture, which is recognized by The National Institutes of Health as an effective complementary therapy. In Bibis Luhur RW XXII, many residents complain of pain, particularly in the lower back, shoulders, spine, and knees, caused by illness, physical activity, work, or age factors. Community service activities were conducted using counseling methods on the types of musculoskeletal pain, their causes, and how to manage them. Additionally, demonstrations of muscle and joint stretching, as well as acupuncture services and the application of pain relief oil, were provided. The results showed that of the 22 participants, the majority were aged 60-64 years and complained of pain in the arms and legs. The therapy conducted successfully reduced the average pain scale from 5.0 in the first session to 2.1 in the fourth session. In conclusion, this community service was effective in increasing residents' knowledge about musculoskeletal pain and reducing pain intensity among the residents of Bibis Luhur RW XXII, Surakarta.